Supercritical Impregnation of Cinnamaldehyde into Polylactic Acid as a Route to Develop Antibacterial Food Packaging Materials - Guarda-Moraga, A; Valenzuela-Bascunan, X; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Lopez de Dicastillo-Bergamo, A; Villegas-Vallejos, C (Elsevier Ltd, 2017)
Supercritical impregnation was used to incorporate a natural compound with antibacterial activity into biopolymer-based films to develop active food packaging materials. Impregnation tests were carried out under two pressure conditions (9 and 12 MPa), and three depressurization rates (0.1, 1 and 10 MPa min− 1) in a high-pressure cell at a constant temperature equal to 40 °C. Cinnamaldehyde (Ci), a natural compound with proven antimicrobial activity, was successfully incorporated into poly(lactic acid) films (PLA) using supercritical carbon dioxide (scCO2), with impregnation yields ranging from 8 to 13% w/w. Higher pressure and slower depressurization rate seem to favor the Ci impregnation. The incorporation of Ci improved thermal, structural and mechanical properties of the PLA films. Impregnated films were more flexible, less brittle and more resistant materials than neat PLA films. The tested samples showed strong antibacterial activity against the selected microorganisms. In summary, this study provides an innovative route to the development of antibacterial biodegradable materials, which could be used in a wide range of applications of active food packaging. © 2017 Elsevier Ltd